P255 Perceived disease severity and treatment satisfaction among patients with ulcerative colitis in Europe. (25th January 2019) - Armuzzi, A; Tarallo, M; Bargo, D; Lucas, J; Bluff, D; Hoskin, B; Salese, L; Cappelleri, J; Kayhan, C; DiBonaventura, M
Abstract: Background: Although ulcerative colitis (UC) trials emphasise rectal bleeding and stool frequency as subjective disease activity measures, there are many clinical manifestations of UC. The current study explored how patients perceive their disease severity and treatment experiences, and how these perceptions are related to symptom reporting. Methods: Data from the 2015 and 2017 Adelphi Inflammatory Bowel Disease Specific Programmes (IBD-DSP) were used. The IBD-DSP is a database of patient chart information abstracted by gastroenterologists across the European Union Five (ie, France, Germany, Italy, Spain, and the UK). Eligible gastroenterologists were asked to complete patient record forms for their next seven consecutive eligible adult patients with UC. Patients were then invited to complete a survey including their disease perceptions and symptom experiences. Only patients with moderate-to-severe UC were included in the analysis (defined as those who had used either an immunomodulator or a biologic). The concordance between physician and patient perceptions of current severity was examined as well as the relationship between disease severity, treatment satisfaction, and symptom reporting. Statistical differences among groups were examined using chi-square and one-way analysis of variance tests. Results: In total, 518 patient record forms with linked surveys were included (55.2% male, mean age: 38.7 years, mean disease duration = 4.9 years). Physicians categorised their patients as 51.0% mild, 44.7% moderate, and 4.3% severe; patients assessed their severity as 48.0% mild, 45.5% moderate, and 6.5% severe (kappa = 0.64; moderate agreement). Of the 23 symptoms assessed, 18 varied significantly ( p < 0.05) by patient self-reported severity. UC-related symptoms were common even among patients who perceived their disease as mild: rectal urgency = 14.5%, bloody diarrhoea = 10.0%, and tenesmus = 10.0%. Additionally, 11.2% of these patients reported their current pain level at 5 or above (worse) on a 0–10 numerical rating scale; 10.3%, 9.7%, and 20.3% reported their sleep disturbance, sexual dysfunction and fatigue levels, respectively, at 5 or above (worse). Similar findings were observed for treatment satisfaction; 18 of 23 symptoms varied significantly ( p < 0.05) by satisfaction levels. Patients who reported being satisfied and 'at the best level of what treatment can achieve' still reported a number of UC-related symptoms: rectal urgency = 18.1%, bloody diarrhoea = 16.1%, and tenesmus = 14.5%. Conclusions: Large proportions of patients in Europe with a history of advanced therapy perceive their disease severity to be mild and are satisfied with their current therapy. Nonetheless, even among these patients, symptoms remain.